PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR KIMIA TAHUN 2017-2019 - Rosalinda Hutapea; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
Corporate Tax Avoidance is a way of limiting or eliminating the tax burden by considering the tax risks it causes. This study aims to examine and provide evidence of the influence of corporate governance, profitability, and leverage on tax avoidance. The population in this study is the chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sample in this study used 13 chemical companies listed on the Indonesia Stock Exchange as many as 39 samples. This data was downloaded from www.idx.co.id. The methods used in this research are descriptive analysis method, classical assumption test, significant T test and F significant test, normality test, and linear regression analysis, with a significance level of 0.05 or u. 5%. The results of this study indicate that corporate governance has a positive and insignificant effect on tax avoidance 0.625> 0.05 with t count 0.493, profitability has a negative and significant effect on tax avoidance 0.019> 0.05 with t count -2.450, and leverage has a negative but not negative effect. significant to tax avoidance 0.438> 0.05 with t count -784.